A versatile nanoagent for multimodal imaging-guided photothermal and anti-inflammatory combination cancer therapy. (10th June 2021) - Yan, Ping; Shu, Xian; Zhong, Hao; Chen, Peiling; Gong, Haiyan; Han, Shisong; Tu, Yingfeng; Shuai, Xintao; Li, Jie; Liu, Li-Han; Wang, Ping
Abstract : A versatile tumor targeting theranostic nanoagent (named T-lipos-CPAuNCs) was introduced to realize multimodal imaging-guided cancer photothermal therapy with suppression of the inflammatory response. Abstract : Photothermal therapy (PTT) has drawn great attention in cancer treatment because of its minimal invasiveness and high spatiotemporal selectivity, but it still encounters severe obstacles like heat-resistance, metastasis and recurrence. A key reason for the treatment failure is the highly inflammatory tumor microenvironment caused by hyperthermia. A simultaneous anti-inflammatory therapy alongside the PTT has great potential for overcoming the drawbacks of PTT; however, it has been less reported and further study is urgently needed. In addition, as many inorganic photothermal agents have no inherent imaging capability, diagnostic strategies should be introduced to help identify cancerous lesions and find the best treatment time period for PTT. Herein, we developed a versatile theranostic nanoagent (named T-lipos-CPAuNCs) for synergistic multimodal imaging-guided photothermal/anti-inflammatory cancer therapy. Perfluorohexane (PFH) loaded AuNCs and the anti-inflammatory drug celecoxib were encapsulated into the tumor-targeting cyclic Arg-Gly-Asp (cRGD) peptide modified liposomes to form T-lipos-CPAuNCs. The T-lipos-CPAuNCs accumulated in the tumor tissue and selectively targeted the cancer cells, and converted photo to thermal energy under near-infrared (NIR) laser irradiation to kill the cancer cells by PTT. The high temperature further accelerated the release of celecoxib to exert an anti-inflammatory effect, while on the other hand led to liquid to gas phase transition of PFH to facilitate ultrasound (US) imaging. The T-lipos-CPAuNCs also exhibited photoacoustic (PA) imaging capability. In vitro and in vivo experiments established that under the guidance of multimodal imaging, T-lipos-CPAuNCs significantly suppressed the tumor growth by PTT and prevented tumor metastasis with non-apparent tumor inflammation. The developed theranostic nanosystem (T-lipos-CPAuNCs) shows great potential for PA/US multimodal imaging guided photothermal/anti-inflammatory combination cancer therapy.